Can malaria protein fight cancer? - Mannaa, Fathia Abd Elwahid (Comunicata Scientiae, 2018)
Cancer risk depends on a combination of our genes, environment and other aspects of our lives, many of which we can control. Surgery, radiation and chemotherapy are often effective at treating people with a solid tumor, but once the cancer has spread and formed tiny tumors at distant sites, chances for a successful recovery are dismal.Recently, it was discovered that the malaria parasite, Plasmodium falciparum produce and present a malarial protein called VAR2CSA, which bind a type of sugar molecule exclusively found in the placenta. It was found that the exact same sugar molecule structure is also found in most cancer cells. Both molecules are a type of chondroitin sulfate. The VAR2CSA only adhere in the placenta and do not bind to chondroitin sulfate expressed elsewhere in the body. In tumors, placental-like chondroitin sulfate chains are linked to a limited repertoire of cancer-associated proteoglycans including CD44 and CSPG4. The recombinant VAR2CSA (rVAR2) protein localizes to tumors in vivo and rVAR2 fused to diphtheria toxin or conjugated to hemiasterlin compounds strongly inhibits in vivo tumor cell growth and metastasis.